The Role of Assistive Technology in Supporting Communication and Academic Access for Deaf Students: A Qualitative Study at Gallaudet University - Alhulays, Sarah Abed (Baileo: Jurnal Sosial Humaniora, 2024)
The biggest challenge faced by deaf students in education is the limited access to verbal communication, which affects their participation in learning. Communication technology and translation solutions are viewed as potential remedies, but their application in educational settings remains suboptimal. This study highlights the importance of exploring and identifying the most effective assistive technologies to support the communication and academic access of deaf students, with the goal of creating an inclusive and empowering learning environment that enhances their academic outcomes. The research methodology employed a qualitative approach, with in-depth interviews conducted with 10 teachers at Gallaudet University to gain deep insights into the most relevant and effective assistive technologies. The findings indicate that communication technology and translation solutions, such as mobile applications, iCloud services, and sign language, have great potential to support learning, help deaf students efficiently translate educational content, and facilitate knowledge sharing in the classroom. In conclusion, assistive technologies play a significant role in improving the communication and translation abilities of deaf students, thereby contributing to their academic achievement.